2017
DOI: 10.1007/s11255-017-1697-5
|View full text |Cite
|
Sign up to set email alerts
|

Addition of silymarin to renin–angiotensin system blockers in normotensive patients with type 2 diabetes mellitus and proteinuria: a prospective randomized trial

Abstract: Silymarin did not show a significant reduction in the primary and secondary outcomes. Importantly, silymarin treatment was associated with a significant reduction in the hospitalization rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Our results on blood lipids (TC, TG, LDL-C, and HDL-C) were in line with the study of Mohammadi et al [19] who integrated 10 clinical trials. However, there were differences compared with the study of Hadi et al [16] who reported that silymarin supplementation did not significantly reduce FBG, TC, and TG using 7 trials and the study of Voroneanu et al [23] who used 5 RCTs to reveal silymarin supplementation had no effects on lipid profile (TC, TG, and HDL-C). These discrepancies may be resulted from an increased sample size in our study.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Our results on blood lipids (TC, TG, LDL-C, and HDL-C) were in line with the study of Mohammadi et al [19] who integrated 10 clinical trials. However, there were differences compared with the study of Hadi et al [16] who reported that silymarin supplementation did not significantly reduce FBG, TC, and TG using 7 trials and the study of Voroneanu et al [23] who used 5 RCTs to reveal silymarin supplementation had no effects on lipid profile (TC, TG, and HDL-C). These discrepancies may be resulted from an increased sample size in our study.…”
Section: Discussionmentioning
confidence: 66%
“…Finally, 16 studies fulfilled the eligibility criteria and were included for this meta-analysis. [ 12 13 14 15 22 23 24 25 26 27 28 29 30 31 32 33 ]…”
Section: Resultsmentioning
confidence: 99%
“…In addition, combined therapy of Chinese herbal medicine and ACEI/ARB could exert a greater beneficial action on proteinuria, UAER, urinary albumin to creatinine ratio (UACR) and urinary protein to creatinine ratio than ACEI/ARB alone 19 . Besides the details demonstrated below, the results from those studies investigating the clinical efficacies of Chinese medicine on DN are also displayed in the Supporting Information Table S1 13 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 .…”
Section: Clinical Efficacies Of Chinese Medicines In Dn Treatmentmentioning
confidence: 99%
“…Some bioactive phytochemicals contained in Chinese medicines have been extracted and isolated using modern technologies, then developed as principal or adjuvant therapies and widely used for the purpose of treating DN. Modern pharmacological researches and clinical trials have demonstrated the therapeutic effects of these phytochemicals, mainly belonging to the classic of polyphenols (breviscapine, puerarin, resveratrol, safflower yellow, silymarin), alkaloids (berberine, ligustrazine, paeony glucosides, tripterygium glycosides) and hydroxyanthraquinones (emodin) that are discussed below in order 30 , 31 , 32 , 33 , 34 , 35 , 54 , 55 , 56 , 57 .…”
Section: Clinical Efficacies Of Chinese Medicines In Dn Treatmentmentioning
confidence: 99%
See 1 more Smart Citation